Skrining Fitokimia dan Penetapan Kadar Flavonoid Total Ekstrak Biji Kopi Robusta (Coffea canephora) asal Lampung Barat - Kiki Yuli Handayani; Rudi Setiawan; Agitha Casanova Capah; Natasya Armelia Putri; Peggy Ivana Prayuda; Suci Fitria (Sinteza, 2026)
Robusta coffee (Coffea canephora) is one of Indonesia’s leading agricultural commodities, with West Lampung serving as a major production center. Besides its economic significance, robusta coffee has garnered scientific attention due to its potential as a source of bioactive compounds. Among these, flavonoids stand out for their well-documented antioxidant, anti-inflammatory, and anti-aging properties, making them highly relevant for applications in cosmetic and personal care products, particularly in hair care formulations. Flavonoids are known to play a crucial role in maintaining scalp health, preventing oxidative damage to hair follicles, and promoting overall hair vitality. This study aimed to investigate the phytochemical profile and quantify the total flavonoid content in Coffea canephora bean extract originating from West Lampung. Phytochemical screening was conducted qualitatively to detect the presence of secondary metabolites such as alkaloids, tannins, saponins, and flavonoids. For the quantification of total flavonoid content, a UV-Visible spectrophotometric method was employed, using quercetin as the standard reference compound. The extract was first macerated with 96% ethanol, followed by filtration and evaporation to obtain a concentrated sample. The results revealed the presence of key bioactive compounds, including tannins, saponins, and notably, flavonoids. The total flavonoid content was found to be 784 mg QE/g extract. These findings support the potential utilization of Coffea canephora from West Lampung as a functional raw material in cosmetic formulations, particularly for hair care products aimed at protecting against oxidative stress and enhancing scalp and hair health. Further studies are recommended to explore the extract’s mechanism of action and its compatibility in cosmetic bases.